Puisi “لا بد أن أستأذن الوطن” Karya Nizar Qubbani Dalam Bingkai Stilistika - Ashief El Qorny; Khasanah Khasanah; Rufaida Hindun Farhisiyati; Ahmad Rois (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2022)
This paper aims to examine the style of language used by Nizar Qubbani in his poetry with the theme of modern life by describing the main idea or theme, elements of feeling or emotion, and style of language based on aspects of diction or choice of words, syntax or sentence structure, and rhetorical aspects or meaning. . This article is a literature study which is analytically descriptive in nature by referring to the text of Nizar Qubbani's poetry as the primary source. The method of data analysis is content analysis with a stylistic approach to examining and analyzing the style of the poem's language. The stylistic theory put forward by Gorys Keraf will be used in understanding the types of diction, and language style based on syntactic aspects and rhetorical aspects or meaning. Poetry with the theme of "life picture" with a diction that maintains aesthetic value is supported by a very strong style of language. The style of language in the poem is very strong in accordance with the characteristics of the neoclassical poetry school pioneered by Nizar Qubbani at that time, free but still strongly holding on to wazan and qafiyah. From the aspect of diction, the words chosen in this poem are quite easy to understand, with a popular word style.